Reading genesis: beginnings - Kissileff, Beth (Biblical studies, 2016)
"This new collection fills Genesis with meaning, gathering intellectuals and thinkers who use their professional knowledge to illuminate the Biblical text. These writers use insights from psychology, law, political science, literature, and other scholarly fields, to create an original constellation of modern Biblical readings, and receptions of Genesis: A scientist of appetite on Eve's eating behavior; law professors on contracts in Genesis and psychologists on facial recognition; an anthropologist on end of life issues and a historian on the nature of human strife in the Cain and Abel story; political scientists on the nature of Biblical games, Abraham's resistance and collective action"--